Directory of Occupational Education Programs in New York State - New York State Education Dept., Albany. Office of Occupational and Continuing Education; New York State Education Dept., Albany. Office of Occupational and Continuing Education ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1972)
Contained in this alphabetized, occupational education directory are the names of secondary and post-secondary education programs offered by New York's public and private institutions. Listed alphabetically by county, only licensed, registered, or approved schools and programs are included. (SN)
Educational level discussed: Postsecondary Education.
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Directories; Educational Programs; Postsecondary Education; Proprietary Schools; Public Schools; Secondary Education; Vocational Education; Vocational Schools; Vocational Training Centers; New York